Artificial intelligence – the next frontier in IT security?. Issue 4 (April 2017) - Talwar, Rohit; Koury, April
Abstract : Security has always been an arms race between attacker and defender. He starts a war with a stick, you get a spear; he counters with a musket, you upgrade to a cannon; he develops a tank, you split the atom. While the consequences of organisational cyber-security breaches may not be as earth-shatteringly dramatic today, the arms race of centuries ago continues into the digital sphere of today.